Assessment of Antibiotic Efficacy in the Management of “Priority 1: Critical” Multi-Drug Resistant Gram-Negative Bacterial Infections Enlisted by WHO - M, Morey Komal; Balakeshwa, Ramaiah; B. R, Prabhudev (Indian Journal of Pharmacy Practice)
Background: The growing resistance pattern of multidrug-resistant gram-negative bacteria is increasing, making it more crucial to use antibiotics. Our study focuses on antibiotics’ rational use and efficacy for gram-negative bacterial infections. aim to find the susceptibility and the resistance pattern of the gram-negative bacteria-P. aeruginosa, K. pneumoniae, A. baumannii, and E. coli (Priority 1: Critical) to the antibiotics and to assess the antibiotic efficacy. Materials and Methods: It is a prospective observational study performed using an antibiogram to find susceptibility and the right use of the antibiotic for Priority 1: Critical species of gram-negative bacteria. The study involved 201 people and was carried out over a period of nine months. Statistical analysis was performed with the help of JASP software. Results: Escherichia coli being the highest gram-negative causing bacterial infections have also made it very challenging to treat the infections due to its growing resistance pattern. our study showed that Cefoperazone+sulbactam and piperacillin+tazobactam are the most susceptible drugs. The highest-resistant drugs are carbapenem, meropenem, ampicillin and ertapenem. Student-paired T-test was performed for CRP, Procalcitonin and ESR; the results were statistically significant. Conclusion: This study interprets the growing and new pattern of MDR that has made it a very challenging aspect of the healthcare system. It emphasizes the appropriate usage of antibiotics for better infection control and good patient outcomes.
Keywords: MDR bacterial infection; Gram-negative bacterial infection; Antibiotic in MDR; JASP software